2018
DOI: 10.1021/jacs.8b06664
|View full text |Cite
|
Sign up to set email alerts
|

Could Mesophases Play a Role in the Nucleation and Polymorph Selection of Zeolites?

Abstract: Zeolites and mesoporous silicas are porous materials with important applications in catalysis, gas storage, and separation. Zeolite crystals form in the presence of cationic surfactants that act as structure directing agents (SDAs). The way SDAs control the nucleation and polymorphs selection in zeolites is not fully understood. The formation of mesoporous silica is templated by liquid crystalline mesophases that result from frustrated attraction between silicates and long-chain SDAs. Experiments indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(90 citation statements)
references
References 177 publications
(403 reference statements)
1
89
0
Order By: Relevance
“…This "Zeolite Sorting Hat" tackles data scarcity by using flexible and unbiased SOAP structural descriptors as inputs, and relatively simple and robust linear classification As it is the cases for many synthetic tasks, making zeolites is a form of art, guided by experience, chemical intuition and serendipity. The Zeolite Sorting Hat introduces datadriven techniques and rationale design [32,33] into the process of selecting candidates that we hope will accelerate the rate of discovery, which in turn will improve the predictive capabilities of the model in a positive feedback mechanism that will progressively take the guesswork out of zeolite synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…This "Zeolite Sorting Hat" tackles data scarcity by using flexible and unbiased SOAP structural descriptors as inputs, and relatively simple and robust linear classification As it is the cases for many synthetic tasks, making zeolites is a form of art, guided by experience, chemical intuition and serendipity. The Zeolite Sorting Hat introduces datadriven techniques and rationale design [32,33] into the process of selecting candidates that we hope will accelerate the rate of discovery, which in turn will improve the predictive capabilities of the model in a positive feedback mechanism that will progressively take the guesswork out of zeolite synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, Kumar et al suggested ways to find a new guest-free zeolitic ice: (1) incorporation of attractive guests, (2) application of pressure, and (3) relief of the strain in the water network via incorporation of other hydrogen-bonded molecules or ions. 51 Our approach can be classified in the first category. A solid surface of material can stabilize water and promote formation of zeolitic ices.…”
Section: Resultsmentioning
confidence: 99%
“…The faculty published 2 peer‐reviewed books, [ 238,239 ] 9 peer‐reviewed book chapters, [ 240–248 ] and 115 peer‐reviewed research papers. [ 249–363 ] This comes to 1.6 peer‐reviewed products/faculty/year during the 3‐year grant period, which is 3.2 times the rate of publication for natural science faculty at PUIs. [ 46 ]…”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%
“…One of the challenges to the overall undergraduate research movement is that the ability of undergraduate research to advance scientific knowledge remains undervalued. [ 364,365 ] From 2001, when the first NSF‐MRI grant was funded, through the summer of 2019, the MERCURY investigators have published 361 peer‐reviewed publications, including 2 in Chemical Society Reviews , [ 104,269 ] 1 in Chemical Reviews , [ 41 ] 1 in Nature Reviews Chemistry , [ 328 ] 3 in Science , [ 160,184,272 ] 2 in Nature , [ 271,344 ] 2 in Angewandte Chemie International Edition , [ 199,346 ] 13 in JACS , [ 20,24,26,36,59,71,84,112,136,169,289,315,336 ] and 3 in PNAS . [ 5,148,318 ] We published 44 papers during the first MRI grant period, [ 2–45 ] 50 during the second MRI grant period, [ 47–96 ] 62 during the third MRI grant period, [ …”
Section: Research Accomplishments (Intellectual Merit) and Transformamentioning
confidence: 99%